"Now about these masochistic tendencies - when did you first notice that you actually enjoyed attending the Eskimo games?" - Uluschak, Edd (Edmonton Journal, 1969)
"Now about these masochistic tendencies - when did you first notice that you actually enjoyed attending the Eskimo games?"